Local Labor Markets Dynamics and Export Shocks: Theory and Evidence from Indonesia - Carlos Góes; Juan Segnana; Raymond Robertson; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2023)
We study the dynamic effects of export exposure over local labor markets in Indonesia. We develop an empirical strategy to instrument exposure to exports using exposure to foreign demand shocks and validate it showing that the labor market responses are consistent with those expected from demand shocks in a spatial model. Export shocks unambiguously increase employment in Indonesia. While effects on average income per employee are ambiguous due to industry- and sectoral-compositional effects, our estimates of district-level welfare suggest that export shocks induce an increase in welfare.
Keywords: F16; J16; O19; 330; international trade; labor markets; inequality; poverty; jobs